Humic acids enhance salt stress tolerance associated with pyrroline 5-carboxylate synthetase gene expression and hormonal alteration in perennial ryegrass (Lolium perenne L.) - Meng, Qiuxia; Yan, Min; Zhang, Jiaxing; Zhang, Qiang; Zhang, Xunzhong; Yang, Zhiping; Luo, Yuan; Wu, Wenli (Frontiers in Plant Science, 2023)
Humic acid (HA) has been used as an important component in biostimulant formulations to enhance plant tolerance to salt stress but the mechanisms underlying are not fully understood. This study was to investigate physiological and molecular mechanisms of HA's impact on salt stress tolerance in perennial ryegrass (Lolium perenne L.). The two types of HA were extracted from weathered coal samples collected from Wutai County (WTH) and Jingle County (JLH) of Shanxi Province, China. The grass seedlings subjected to salt stress (250 mM NaCl) were treated with HA solutions containing 0.01% WTH (W/V) or 0.05%JLH (W/V), respectively. The HA treatments improved leaf photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), reduce leaf oxidative injury (lower malondialdehyde content), Pro and intercellular CO2 concentration in salt-stressed perennial ryegrass. The HA treatments also reversed the decline in antioxidative enzymes ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD), superoxide dismutase (SOD) activity, and improved growth and anti-senescence hormones indole-3-acetic acid (IAA) and brassinosteroid (BR). The HA treatments reduced relative expression of P5CS and its downstream products proline (Pro) and the stress defense hormones abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA), and polyamines (PA). The results of this study indicate that the application of HAs may improve salt stress tolerance by regulating P5CS gene expression related to osmotic adjustment and increasing the activity of antioxidant enzymes and anti-senescence hormones in perennial ryegrass.